2019
DOI: 10.1016/j.ijggc.2019.102840
|View full text |Cite
|
Sign up to set email alerts
|

Impact of CO2 injection on wettability of coal at elevated pressure and temperature

Abstract: Injection of carbon dioxide (CO 2 ) into coal seams has been demonstrated as an effective technology for enhanced methane recovery and CO 2 storage. However, the impacts of the geochemical reactions between CO 2 and coal on the wettability of coal pore surfaces, which influences immiscible multiphase displacement, are not yet well understood. We studied wettability alterations of coal surfaces resulting from reactions with gas, liquid and supercritical (sc)CO 2 under varied pressure (1-141 bar) and temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 37 publications
3
19
0
Order By: Relevance
“…This proves that high-rank coals are the best candidates for CO 2 sequestration and CH 4 recovery at high pressure and low temperature due to increased CO 2 wettability. Similar results were reported by ref . However, they found that injecting liquid and Sc-CO 2 influenced CO 2 wettability compared to CO 2 gas.…”
Section: Wettability Alteration During Co2-ecbm Technology Applicationsupporting
confidence: 89%
“…This proves that high-rank coals are the best candidates for CO 2 sequestration and CH 4 recovery at high pressure and low temperature due to increased CO 2 wettability. Similar results were reported by ref . However, they found that injecting liquid and Sc-CO 2 influenced CO 2 wettability compared to CO 2 gas.…”
Section: Wettability Alteration During Co2-ecbm Technology Applicationsupporting
confidence: 89%
“…36 Therefore, the irreducible water saturation in the CO 2 −water system was smaller than that in the He/CH 4 −water system. In addition, the previous study found that the CO 2 /water/coal contact angles increased slightly with pressure, 37 which indicated that the water mobility was enhanced as the pressure increased. Thus, the irreducible water saturation in the CO 2 −water system decreased with an increase in displacement pressure.…”
Section: Effect Of Displacement Pressure and Gas Type On The Relative...mentioning
confidence: 96%
“…Detailed experimental procedures are mentioned in our previous work. 45,46 2.3.3. Bubble Image Analysis.…”
Section: Contact Angle Measurement Proceduresmentioning
confidence: 99%
“…45 and 60 °C were 8.65 and 4.77, respectively. The static contact angles were greater at low temperatures and more significantly affected by pressure according to the filled area.…”
mentioning
confidence: 95%